2018
DOI: 10.1021/acs.chemrev.7b00582
|View full text |Cite
|
Sign up to set email alerts
|

In Situ, Time-Resolved, and Mechanistic Studies of Metal–Organic Framework Nucleation and Growth

Abstract: The vast chemical and structural diversity of metal-organic frameworks (MOFs) opens up the exciting possibility of "crystal engineering" MOFs tailored for particular catalytic or separation applications. Yet the process of reaction discovery, optimization, and scale-up of MOF synthesis remains extremely challenging, presenting significant obstacles to the synthetic realization of many otherwise promising MOF structures. Recently, significant new insights into the fundamental processes governing MOF nucleation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
411
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(443 citation statements)
references
References 250 publications
4
411
0
Order By: Relevance
“…[7b-f] In general, it is very difficult to retain as trong Brønsted acid site such as phosphoric acid in MOFs,which is mainly due to spontaneous deprotonation of the acids in solution, which leads to direct metal-acid coordination. [9] Unfortunately,w ith af ew notable exceptions such as MIL-100 and MIL-101, [10] most of the reported MOFs are decomposed under such harsh conditions.I tr emains ac hallenge to design chiral Brønsted acid type of MOF catalysts.T oa ddress this issue,h ere we show that phosphoric acids can be introduced into MOFs by sterically protecting them from coordination. [9] Unfortunately,w ith af ew notable exceptions such as MIL-100 and MIL-101, [10] most of the reported MOFs are decomposed under such harsh conditions.I tr emains ac hallenge to design chiral Brønsted acid type of MOF catalysts.T oa ddress this issue,h ere we show that phosphoric acids can be introduced into MOFs by sterically protecting them from coordination.…”
Section: Introductionmentioning
confidence: 99%
“…[7b-f] In general, it is very difficult to retain as trong Brønsted acid site such as phosphoric acid in MOFs,which is mainly due to spontaneous deprotonation of the acids in solution, which leads to direct metal-acid coordination. [9] Unfortunately,w ith af ew notable exceptions such as MIL-100 and MIL-101, [10] most of the reported MOFs are decomposed under such harsh conditions.I tr emains ac hallenge to design chiral Brønsted acid type of MOF catalysts.T oa ddress this issue,h ere we show that phosphoric acids can be introduced into MOFs by sterically protecting them from coordination. [9] Unfortunately,w ith af ew notable exceptions such as MIL-100 and MIL-101, [10] most of the reported MOFs are decomposed under such harsh conditions.I tr emains ac hallenge to design chiral Brønsted acid type of MOF catalysts.T oa ddress this issue,h ere we show that phosphoric acids can be introduced into MOFs by sterically protecting them from coordination.…”
Section: Introductionmentioning
confidence: 99%
“…In‐situ methods have been shown to be a versatile tool to investigate such findings during the synthesis of solids from a liquid . Particularly in‐situ powder X‐ray diffraction (PXRD) experiments have emerged in recent years for the investigation of the synthesis of various materials like oxides, phosphates, phosphonates, oxometallates and also for the synthesis of MOFs . Using synchrotron X‐ray radiation, it is possible to measure PXRD patterns with high temporal resolution in‐situ during the synthesis and thus gain important information, especially about the occurring crystalline products.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the use of modulators in crystal and defect engineering has been extensively studied in the past. In particular, Kitagawa and co‐workers as well as other research groups revealed how monodentate carboxylic acids, among many other factors, such as the presence of ions or surfactants in solution, pH, solvent, ultrasound, or even acoustic waves, can steer the kinetics of the growth of either the {100} or {111} facet in HKUST‐1 with a subsequent change in the morphology from cubic to cuboctahedral and eventually to octahedral. In this study, to understand the effect on morphology of co‐crystallizing the BTC and CYDC ligands under solvothermal conditions, we performed scanning electron microscopy (SEM) on the materials synthesized.…”
Section: Resultsmentioning
confidence: 99%